PEWARISAN SASTRA LISAN KABHANTI GAMBUSU - La Sudu (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
The inheritance of kabhanti gambusu is the process of passing knowledge about kabhanti gambusu from one generation to the next, carried out both formally and informally. Formal inheritance is the process of learning kabhanti gambusu conducted by school teachers for their students (the younger generation), while informal inheritance of kabhanti gambusu is the process of passing knowledge by kabhanti gambusu practitioners to young prospective performers in order to become professional performers. The sustainability and continuity of kabhanti gambusu depend on its inheritance; in other words, it depends on the community's concern, especially the speakers or tradition practitioners, to pass it on to the next generation. The problem of inheritance becomes more severe because kabhanti gambusu naturally does not progress smoothly. If this inheritance problem is hindered, the existence of an oral literature is on the path to extinction.